Cracking the Code: The Impact of Orthographic Transparency and Morphological-Syllabic Complexity on Reading and Developmental Dyslexia - Borleffs, Elisabeth; Maassen, Ben A. M.; Lyytinen, Heikki; Zwarts, Frans (Frontiers in Psychology, 2019)
Reading is an essential skill in modern societies, yet not all learners necessarily become proficient readers. Theoretical concepts (e.g., the orthographic depth hypothesis; the grain size theory) as well as empirical evidence suggest that certain orthographies are easier to learn than others. The present paper reviews the literature on orthographic transparency, syllabic complexity, and morphological complexity of alphabetic languages. These notions are elaborated to show that differences in reading acquisition reflect fundamental differences in the nature of the phonological recoding and reading strategies developing in response to the specific orthography to be learned. The present paper provides a narrative, cross-linguistic and integrated literature review, thereby contributing to the development of universal reading models and at the same time pointing out the important differences between orthographies at the more detailed level. Our review also yields suggestions to devise language-specific instruction and interventions for the development of the specific reading strategies required by the characteristics of the orthography being acquired.